Global observations of submesoscale coherent vortices in the ocean. (November 2020) - McCoy, Daniel; Bianchi, Daniele; Stewart, Andrew L.
Abstract: Subsurface-intensified anticyclones are ubiquitous in the ocean, yet their impact on the large-scale transport of heat, salt and chemical tracers is poorly understood. These submesoscale coherent vortices (SCVs) can trap and advect waters thousands of kilometers away from the formation region, providing a transport pathway that is unresolved by low-resolution Earth System Models. However, knowledge of the importance of these eddies for the large scale circulation is hindered by the lack of systematic observations. Here, we take advantage of the global network of Argo floats to identify occurrences of these eddies, which appear as weakly stratified anomalous water masses with Gaussian-shaped vertical structures. We develop a general algorithm to detect subsurface eddies that have propagated away from their source region, and apply it to the database of Argo float profiles, resulting in roughly 4000 detections from more than 20 years of observations. We further group detections into regional populations to identify hot-spots of generation and mechanisms of formation. Analysis of regional SCV statistics reveals important sites of SCV generation in Eastern Boundary Upwelling Systems, marginal sea overflows, and mode water formation regions along major open-ocean fronts. Because of the heat and salt anomaly contained within their cores, SCV could leave a significant imprint on the hydrographic properties of water masses in regions of high SCV density. Highlights: We develop and apply a new algorithm to detect submesoscale coherent vortices (SCVs) from Argo float profiles throughout the global ocean. We identify and characterize regional SCV populations with consistent hydrographic properties. We link notable SCV populations to their mechanisms of formation, and quantify their impact on regional hydrography.